(untitled) (Homoeopathy for All, 2021)
Psoriasis is a chronic proliferative and inflammatory condition that affects the skin and sometimes the nails and joints. It occurs due to a problem with the immune system that results in an overgrowth of skin cells, leading to skin changes. This makes the skin build up into bumpy red patches covered with white scales. They can grow anywhere, but most appear on the scalp, elbows, knees, and lower back. It can’t be passed from person to person. There are several subtypes of psoriasis but the plaque type is the most common and presents on the trunk, extremities, and scalp. People with psoriasis are more likely to have diabetes, high blood lipids, cardiovascular disease, and a variety of other inflammatory and NCDs.